The association between Planetary Health Diet Index (PHDI) and chronic obstructive pulmonary disease (COPD): the mediating role of dietary inflammatory index (DII) - Hongyang Gong; Kaifeng Zhang; Seok Choi; Shaoqun Huang (BMC Pulmonary Medicine)
Abstract Background Given global changes in the environment and dietary habits, it is critical to understand the potential impact of dietary factors and dietary inflammation on respiratory diseases, including COPD. Studying these relationships can help develop more effective prevention strategies. PHDI is a dietary scoring system designed to balance human health and environmental sustainability by promoting increased consumption of plant-based foods and reduced intake of red meat, sugar, and highly processed foods. In contrast, DII quantifies the inflammatory potential of a diet. This study examines the association between PHDI and COPD and assesses whether DII mediates this relationship. Methods We used subgroup analysis, smooth curve fitting, and multivariable logistic regression to investigate the connection between PHDI and the occurrence of COPD. Furthermore, a mediation analysis was carried out to investigate any possible correlation between DII and the link between PHDI and COPD. Results 30,304 participants were included in this investigation, and 1,498 of them reported COPD events. For every 10-point increase in PHDI and each unit increase in DII was associated with a 9% reduction (OR = 0.91, 95% CI: 0.86, 0.97) and an 8% increase (OR = 1.08, 95% CI: 1.02, 1.13) in the prevalence of COPD, respectively, when all variables were adjusted for using multivariable logistic regression. Additionally, the results remain robust when PHDI and DII are converted to tertile. An investigation of smooth curve fitting showed a linear correlation between the risk of COPD and PHDI. The results of the mediation analysis showed that 17.95% of the relationship between PHDI and COPD was mediated by DII (p = 0.034). Conclusions Higher PHDI levels are associated with a lower prevalence of COPD. Additionally, DII appears to mediate this relationship, suggesting that an anti-inflammatory diet may provide benefits.